APONTAMENTOS SOBRE A (IN) APLICABILIDADE DA PROGRESSÃO DE REGIME PER SALTUM NO BRASIL (REMUNOM, 2023)
This article analyzed the application of regime progression per saltum or per jump as a necessary instrument to guarantee the rights of those who are subjected, notably, to serving custodial sentences and do not receive adequate treatment from the State. For that, a documentary and bibliographical research carried out, with the objective of explaining the theme in a precise way. The results show that prison overcrowding is one of the main factors that portray this deficiency and that the Executive Branch must implement adequate public policies to solve the structural crisis faced in the Brazilian prison system, which has been mitigated by the application of the per saltum progression.